Risk factor analysis of falls in elderly patients at the geriatric and internal medicine clinics of a general hospital: A cross-sectional study - Riana Puspa; Nani Sari Murni; Chairil Zaman (School of Health Sciences Al-Ma'arif, 2025)
Background: Increasing life expectancy has led to a larger elderly population vulnerable to health problems, particularly fall risk. Falls in older adults can result in injury, disability, and death, thus requiring comprehensive risk analysis. Objective: This study aimed to analyze risk factors associated with falls among elderly patients in the Geriatric and Internal Medicine Clinics of a General Hospital. Methods: A cross-sectional quantitative study was conducted among 85 elderly respondents at Dr. Rivai Abdullah General Hospital, Banyuasin. Data were collected using structured questionnaires, environmental observation, and medical records. Data analysis consisted of univariate, bivariate using Chi-Square test, and multivariate logistic regression. Results: Multivariate analysis revealed that independence level was the most dominant factor significantly associated with fall risk (p=0.000; OR=0.176; 95% CI=0.069–0.450). Non-independent elderly had a 73.9% probability of experiencing falls. Other factors such as age, gender, education, comorbidities, environment, and polypharmacy showed no significant association (p>0.05). Conclusion: Independence level is the main determinant influencing fall risk in elderly patients. Fall prevention strategies should focus on promoting independence through physical exercise, occupational therapy, family support, and interprofessional interventions. Further studies should explore psychosocial, lifestyle, and nutritional factors.